Penatalaksanaan Leukemia Mieloid Akut pada Dewasa Muda di Daerah Terpencil: Laporan Kasus: Laporan Kasus - Gultom, Clarissa Nadia; Ansori, Said (PT Kalbe Farma Tbk., 2026)
Introduction: Acute myeloid leukemia (AML) is an aggressive and rapidly progressing hematopoietic malignancy that originates from myeloid stem cells in the bone marrow. Case: An 18-year-old male presented with nausea and vomiting for 5 days, preceded by frequent fatigue and weight loss over the past month. Vital signs were within normal limits. Physical examination revealed anemic conjunctivae and palpable enlargement of the liver and spleen. Laboratory examination revealed extreme leucocytosis, severe anemia, and thrombocytopenia. The patient was diagnosed with acute myeloid leukemia. Management was symptomatic with blood transfusion, and referred for further treatment. Discussion: AML is generally characterized by nonspecific symptoms such as anemia, fever, bleeding, hepatosplenomegaly, as well as hematological abnormalities including leukocytosis, anemia, and thrombocytopenia. The diagnosis is made by examining peripheral blood and bone marrow, while the prognosis is influenced by the patient's age, subtype, and cytogenetic abnormalities. Conclusion: AML in young adults may present with nonspecific symptoms such as fatigue, nausea, vomiting, and weight loss, which can delay diagnosis. Marked hematologic abnormalities, including extreme leukocytosis, severe anemia, and thrombocytopenia, should raise suspicion for AML. Early recognition, appropriate supportive management, and timely referral from peripheral healthcare facilities are essential to improve patient outcomes and survival.